Bediuzzaman Said Nursi's approach on women’s issues in Risale-I Nur - Ishak, Mohd Haeqal; Ahmad, Nadzrah; Fadzil, Ammar; Musa, Muhammad Adli; Amir, Ahmad Nabil (2017)
Bediuzzaman Said Nursi addressed many issues on the Muslim way of life in his famous tafsÊr, Risale-I Nur. The discussion and commentaries in this tafsir, which were written during the 1910s and 1950, are still relevant to many present-day issues. This study aims to seek out his opinions on women’s issues as well as his reasoning behind the commandments of the Qur’Én and Sunnah related to them. This study will focus on the chapters and the sub-chapters in Risale-I Nur and their commentaries on women’s issues and proposed solutions. This qualitative study utilizes the deductive and inductive methods, as all of the selected commentaries will be examined and categorised accordingly to the corresponding issue. The result indicates that there are several women’s issues discussed in Risale-I Nur, as well as Bediuzzaman Said Nursi advices on how to utilize women’s potential appropriately.